Потенциальные поля с осевой симметрией и алгебры моногенных функций векторного аргумента. III - Мельниченко, И.П.; Плакса, С.А. (Український математичний журнал, 1997)
Одержано нові зображення потенціалу та функції течії для просторових потенціальних солено-їдальиих полів з осьовою симетрією. Вивчено основні алгебраїчно-аналітичні властивості моно-генних функцій векторного аргумента із значеннями в иескіичеиновимірній банаховій алгебрі парних рядів Фур'є та встановлено зв'язок цих функцій з осесиметричним потенціалом та функцією течії Стокса. Запропонований підхід до опису вказаних полів є аналогом апарату аналітичних функцій у комплексній площині при опису плоских потенціальних полів. We obtain new representations of the potential and flow function of three-dimensional potential solenoidal fields with axial symmetry, study principal algebraic analytic properties of monogenic functions of vector variables with values in an infinite-dimensional Banach algebra of even Fourier series, and establish the relationship between these functions and the axially symmetric potential or the Stokes flow function. The developed approach to the description of the indicated fields is an analog of the method of analytic functions in the complex plane used for the description of two-dimensional potential fields.